Legal Protection of Intellectual Property for Digital Works by Utilizing Emerging Technologies - Bernard Nainggolan; Agus Joko Pramono (Jurnal Hukum, 2025)
The advancement of digital technology has transformed access to information and creativity, enabling widespread distribution of digital works. However, this ease of access has led to significant challenges in enforcing Intellectual Property Rights (IPR), particularly in Indonesia, where legal frameworks like Law Number 28 of 2014 on Copyright and Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions are tested by rampant digital infringements. This study examines the adequacy of existing Indonesian legal frameworks in protecting IPR in the digital era, focusing on gaps in enforcement and regulatory adaptation to emerging technologies such as streaming platforms and Non-Fungible Tokens (NFTs). Using a normative juridical method, this research analyzes relevant statutes, case law, and legal doctrines to assess their effectiveness in addressing digital IPR violations. The findings reveal that while Indonesia has a robust legal foundation, enforcement remains weak due to limited public awareness and inadequate mechanisms for addressing digital-specific infringements. This study emphasizes the need for regulatory reform, enhanced enforcement mechanisms, and targeted education to strengthen IPR protection, fostering innovation and economic competitiveness in Indonesia’s digital landscape.